Pengaruh senam dysmenorrhoea terhadap premenstruasi syndrome pada remaja putri - Sunarsih Sunarsih (Holistik Jurnal Kesehatan, 2022)
Background: Premenstrual syndrome or premenstrual syndrome is a collection of physical, psychological, and emotional symptoms associated with a woman's menstrual cycle. Dysmenorrhoea is the medical term for painful menstruation and about 75 percent of women experience dysmenorrhoea at some point during their reproductive years. Sometimes dysmenorrhoea can be accompanied by nausea, vomiting, diarrhea, and stomach cramps, some women even faint and get drunk, this situation appears severe enough to cause sufferers to experience temporary disruption of activity.Purpose: To determine the effect of exercise for dysmenorrhoea on premenstrual syndrome among teenage girlsMethod: This research was carried out using a quasi-experimental method. The population were all teenage girls students who had premenstrual syndrome (dysmenorrhoea). The research was conducted at senior high school 15 grade X Bandar Lampung. The sample was taken by accidental sampling method of 60 participants divided into the intervention and control groups.Results: Before the intervention, the participants had a pain scale level 56.67 percent moderate pain, after the intervention the pain scale level changed to a mild pain scale of 60 percent.Conclusion: There was a significant difference between the menstrual pain scale before and after dysmenorrhea exercise (p= 0.00 ; 0.05).Suggestion: School institutions are advised to hold dysmenorrhea exercises regularly for students who have premenstrual syndrome.Keywords: Exercise; Dysmenorrhea; Premenstrual syndrome; Teenage girlsPendahuluan: Premenstruasi Syndrom atau sindrom pramenstruasi adalah kumpulan gejala fisik, psikologis dan emosi yang terkait dengan siklus menstruasi perempuan. Dysmenorrhoea adalah istilah medis untuk haid yang terasa nyeri dan sekitar 75 persen wanita mengalami dysmenorrhoea pada suatu saat sepanjang usia reproduksinya. Terkadang dysmenorrhoea dapat disertai dengan rasa mual, muntah, diare dan kram perut, beberapa wanita bahkan pingsan dan mabok, keadaan ini muncul cukup hebat sehingga menyebabkan penderita mengalami gangguan aktivitas untuk sementara.Tujuan: Untuk mengetahui pengaruh senam dysmenorrhoea terhadap premenstuasi syndrome pada remaja putri di SMAN 15 Bandar Lampung.Metode: Penelitian ini dilaksanakan dengan metode quasi experiment. Populasinya seluruh siswi kelas x yang mengalami premenstruasi syndrome (dysmenorrhoea). Penelitian dilakukan di SMAN 15 Bandar Lampung. Sampel penelitian ini diambil dengan metode accidental sampling dengan jumlah sampel 60 partisipan yang dibagai menjadi kelompok intervensi dan kelompok kontrol.Hasil: Sebelum dilakukan intervensi tingkat skala nyeri partisipan adalah nyeri sedang sebanyak 56,67 persen, setelah dilakukan intervensi tingkat skala nyeri berubah menjadi skala nyeri ringan sebanyak 60 persen.Simpulan: Terdapat perbedaan yang bermakna antara skala nyeri haid sebelum dan sesudah senam dysmenorrhoea (p= 0,00 ; α 0,05).Saran: Instansi sekolah disarankan mengadakan senam dysmenorrhoea secara rutin bagi siswi yang mengalami premenstruasi syndrome.